The birth of the orange bodies The emergence of the Santa Fe Community Police as a government program of the police force (Delito y Sociedad, 2021)
This article aims to analyze the political conditions that gave rise to the emergence of the Community Police in the Province of Santa Fe during 2014. From the Foucauldian perspective of governmentality, we understand that this specialized segment is an effect of political disputes to define the police as the central locus in the field of (in)security. The work adopts a qualitative methodology and applies critical discourse analysis in a corpus made up of official documents, journalistic sources and interviews with key informants. With these political discourses we identify the security thematization and the police function built around the Community Police, as well as the strategies and techniques that this unit mobilized to intervene in the field of (in)security. We conclude that the creation of this new force can be read as a government program of the Santa Fe’s police, framed in the paradigm of Democratic Security.
Keywords: Community Police; Democratic Security; Police Government